Peroxisome proliferator-activated receptor agonists (PPARs): a promising prospect in the treatment of psoriasis and psoriatic arthritis - Lima,Emerson de Andrade (2013)
Psoriasis is a polygenic, inflammatory and progressive disease, characterized by an abnormal differentiation and hyperproliferation of keratinocytes, associated with impaired immunologic activation and systemic disorders, while psoriatic arthritis is a chronic inflammatory articular disease. Pathophysiology of psoriasis comprises a dysfunction of the immune system cells with an interactive network between cells and cytokines supporting the initiation and perpetuation of disease and leading to inflammation of skin, enthesis and joints. Recent studies have shown an important role of systemic inflammation in the development of atherosclerosis. Corroborating these findings, patients with severe Psoriasis have marked incidence of psoriatic arthritis, cardiovascular diseases, hypertension, dyslipidemia, obesity and diabetes mellitus, showing an increased risk for acute myocardial infarction, which suggests that the condition is not restricted to the skin. Nuclear receptors are ligand-dependent transcription factors, whose activation affects genes that control vital processes. Among them the peroxisome proliferator-activated receptor is responsible for establishing the relationship between lipids, metabolic diseases and innate immunity. In the skin, peroxisome proliferator-activated receptors have an important effect in keratinocyte homeostasis, suggesting a role in diseases such as psoriasis. The peroxisome proliferator-activated receptors agonists represent a relevant source of research in the treatment of skin conditions, however more clinical studies are needed to define the potential response of these drugs in patients with psoriasis and psoriatic arthritis.